Comparison of Three Immunoassays for the Detection of Myositis Specific Antibodies - Mahler, Michael; Betteridge, Zoe; Bentow, Chelsea; Richards, Michaelin; Seaman, Andrea; Chinoy, Hector; McHugh, Neil (Frontiers in Immunology, 2019)
Objectives: Standardization of myositis specific antibody (MSA) detection is of high importance because these antibodies are relevant for diagnosis and stratification of patients with idiopathic inflammatory myositis (IIM) and have the potential to be used in classification criteria. Many laboratories rely on immunoprecipitation (IP) for the detection of MSA but this approach is compromised by logistic, standardization, and regulatory challenges. Therefore, reliable alternatives to IP are mandatory. Here we aimed compare three methods for the detection of MSA. Methods: Our study initiated from a cohort of 1619 IIM patients (BIRD/University of Bath serology service and UKMyoNet cohorts) and resulted in 157 unique serum samples enriched for higher prevalence of MSA characterized by the laboratory’s routine methods, IP and line immunoassay (LIA: Euroimmun). All samples were tested using a novel fully automated particle-based multi-analyte technology (PMAT, Inova Diagnostics, research use only). Analyses included antibodies to Mi-2, TIF1, PL-12, SAE, EJ, MDA5, PL-7, SRP, NXP2. Results: Overall high agreements were observed between novel methods (LIA and PMAT) and IP (Cohen’s kappa 0.46-0.96) for the detection of MSA. Lowest agreement level of agreement was found for EJ and highest for SAE. Conclusion: The data hold promise for advances in standardization of MSA assays as well as for the potential inclusion of MSA in future classification criteria.